End TB with precision treatment!. Issue 2 (February 2016) - van der Burgt, Evelien P.M.; Sturkenboom, Marieke G.G.; Bolhuis, Mathieu S.; Akkerman, Onno W.; Kosterink, Jos G.W.; de Lange, Wiel C.M.; Cobelens, Frank G.J.; van der Werf, Tjip S.; Alffenaar, Jan-Willem C.
We read with interest the recent Perspective paper by Lönnroth et al. [1] describing a framework for tuberculosis (TB) elimination. In our opinion, monitoring drug exposure by measuring blood concentrations over time (therapeutic drug monitoring (TDM)) may be helpful in contributing to TB elimination in low- and medium-burden setting. TB precision treatment, including optimised drug exposure in relation to drug susceptibility testing, may help end TB http://ow.ly/Utu2u